PEMILIHAN METODE PERAMALAN DALAM MANAJEMEN PERSEDIAAN PRODUK PERTANIAN - Arfina Samangi -; Tomy Perdana - (Politeknik Pertanian Bogor, 2019)
ABSTRACT West Java has cluster of horticulture developed by Padjadjaran University in Lembang and Pangalengan. In 2017, Padjadjaran University in collaboration with TU-Delf, an engineering university in the Netherlands, to create a value co-creation workshop in Ciwidey Sub-district with output forming a vegetable cluster in Ciwidey. In December 2017, two farmer groups that have been established begin to deliver to the modern market through vendors, Locarvest. The buying and selling system agreed by Locarvest and the modern markets is buying and selling where unsold products will be replaced with fresh produce on subsequent shipments. The sale system is very detrimental to Locarvest if there are many vegetables that are returned and cannot be sold anymore because they have deteriorated. Therefore, Locarvest needs to have the ability to forecast market demand to compute the number of product returns. The method used is the time series method with the model forecasting Simple Moving Average, Weighted Moving Average, Basic Exponential Smoothing, Holt, and Arima. The results of this study show the best forecasting model to forecast Locarvest product demand is Weighted Moving Average. The results of the forecasting model can decrease the number of returns by 62.56% from 1,028 packs to 644 packs. In addition, the bullwhip effect also declined by 0.65 from 1.38 to 0,73.ABSTRAKJawa Barat memiliki klaster hortikultura yang dibina oleh Universitas Padjadjaran di Lembang dan Pangalengan. Pada tahun 2017, Universitas Padjadjaran bekerja sama dengan TU-Delf, sebuah universitas teknik di Belanda, untuk membuat sebuah workshop value co-creation di Kecamatan Ciwidey dengan output membentuk suatu klaster sayuran di Ciwidey. Pada Desember 2017, dua kelompok tani yang telah dibentuk mulai melakukan pengiriman ke pasar modern melalui vendor, Locarvest. Sistem jual beli yang disepakati oleh Locarvest dan pasar-pasar modern adalah jual beli tukar guling dimana produk yang tidak terjual akan diganti dengan produk segar pada pengiriman selanjutnya. Sistem penjualan tersebut sangat merugikan Locarvest apabila terdapat banyak sayuran yang dikembalikan dan tidak bisa dijual lagi karena telah mengalami deteriorasi. Oleh karena itu, Locarvest perlu memiliki kemampuan meramal permintaan pasar untuk mengarangi jumlah pengembalian produk. Metode yang digunakan adalah metode time series dengan model peramalan Simple Moving Average, Weighted Moving Average, Basic Exponential Smoothing, Holt, dan Arima. Hasil penelitian ini menunjukkan model peramalan terbaik untuk meramal permintaan produk Locarvest adalah Weighted Moving Average. Hasil model peramalan dapat menurunkan jumlah retur sebesar 62,56% dari 1.028 pack menjadi 644 pack. Selain itu, nilai bullwhip effect juga menurun sebesar 0,65 dari 1,38 menjadi 0,73.